The clinical value of ultrasound in assessing ovarian strangulation in female infants and toddlers with ovarian hernia - Gu, Jiaojiao; Liu, Chen (Frontiers in Pediatrics, 2024)
Objective: To explore the clinical value of ultrasound examination in evaluating the presence of ovarian torsion in female infants with inguinal ovarian hernia. Methods: We conducted a retrospective analysis of 91 cases of ovarian hernia diagnosed by ultrasonography at our institution. Among them, 6 cases were identified as ovarian strangulation, while 85 cases were classified as non-ovarian strangulation. All cases underwent high-frequency ultrasound examination. We analyzed whether there were differences in the associated factors between the two groups and compared the disparities in the urgency of surgery between the two groups. Results: Significant differences were observed between the ovarian strangulation group and the nonstrangulation group in terms of ovarian volume, ovarian blood flow, and the presence of incarceration. The need for emergency surgery was significantly associated with the presence of incarceration and ovarian torsion. Conclusion: Ultrasound has good clinical value in diagnosing ovarian hernia and determining the presence of ovarian strangulation. It can assist clinical physicians in determining the timing of surgery for children with ovarian hernia.